Analysis of the Potentials of Blockchain for the Governance of Global Digital Commons - Rozas, David; Tenorio-Fornés, Antonio; Hassan, Samer (Frontiers in Blockchain, 2021)
In recent years, the increasing need for global coordination has attracted interest in the governance of global-scale commons. In the current context we observe how online applications are ubiquitous, and how emerging technologies enable new capabilities while reshaping sectors. Thus, it is pertinent to ask: could blockchain technologies facilitate the extension and scaling up of cooperative practices and commons management in this global context? In order to address this question, we propose a focus on the most paradigmatic and widely successful examples of global cooperation: global digital commons. Examples of these are the digital resources maintained by large peer production communities, such as free/libre open source software and Wikipedia. Thus, this article identifies and analyses the potentialities of blockchain to support the sustainability and management of global digital commons. Our approach draws on Elinor Ostrom’s classic principles for commons governance, although revisiting and adapting these to the more challenging scope of global digital commons. Thus, in this work we identify the affordances which blockchain provides (e.g. tokenisation, formalisation of rules, transparency or codification of trust) to support the effective management of this type of global commons. As part of our analysis, we provide numerous examples of existing blockchain projects using affordances in line with each principle, as well as potential integrations of such affordances in existing practices of peer production communities. Our analysis shows that, when considering the challenges of managing global commons (e.g. heterogeneity or scale), the potential of blockchain is particularly valuable to explore solutions that: distribute power, facilitate coordination, scale up governance, visibilise traditionally invisible work, monitor and track compliance with rules, define collective agreements, and enable cooperation across communities. These affordances and the subsequent analysis contribute to the emergent debate on blockchain-based forms of governance, first by providing analytical categories for further research, but also by providing a guide for experimentation with the development of blockchain tools to facilitate global cooperation.